Mapping Tour Guides’ Speaking and Writing Skill Levels in Tourist Villages in Trenggalek - Dwi Wahyuningtyas; Wahyu Kyestiati Sumarno; Ria Arista Asih; Fathika Endriana; Khofiatul Rosdiana Windiarti (Nusantara Science and Technology Proceedings, 2022)
Trenggalek is one of the regencies in East Java that is intensively developing tourist villages. By 2022, 35 tourist villages have been successfully built. With the existence of tourist villages with various potentials, supporting factors are needed from not only the government but also the wider community, one of which is the participation of the community as tour guides. A tour guide must master various abilities; communication skills, language skills, and the ability to know a lot about tourist attractions. One of the vital things that must be mastered by a tour guide is the ability to speak and write English as an international language. A tour guide is expected to be able to use English well, fluently, and effectively in carrying out his duties to guide tourists who come. That is why it is necessary to map the level of English proficiency of the tour guides in tourist villages. Thus, this study focused on analyzing the English levels of tour guides in two skills; speaking and writing. The result revealed that tour guides in Trenggalek have a varied range of English speaking and writing levels, from basic to intermediate. It is hoped that later with the mapping of the English level of the tour guides, English teachers and researchers in similar fields will be able to better prepare teaching materials and training programs that are suitable to the needs of the tour guides